Current Status of Infection Prevention and Control Programs for Emergency Medical Personnel in the Republic of Korea - Hyang Soon Oh; Dong Choon Uhm (Korean Society for Preventive Medicine, 2015)
Objectives: Emergency medical personnel (EMPs) are pre-hospital emergency responders who are at risk of exposure to infections and may also serve as a source for the transmission of infections. However, few studies of infection control have specifically addressed EMPs in the Republic of Korea (hereafter Korea). The goal of this study was to assess the current status of infection prevention and control programs (IPCPs) for EMPs in Korea. Methods: A cross-sectional survey was conducted to quantitatively assess the resources and activities of IPCPs. A total of 907 EMPs in five metropolitan cities completed a structured questionnaire from September 2014 to January 2015. The data were analyzed using descriptive statistics, multi-response analysis, and the chi-square test. Results: The mean age of the participants was 34.8±15.1 years. IPCPs were found to have weaknesses with regard to the following resources: the assignment of infection control personnel (ICP) (79.5%), hand hygiene resources such as waterless antiseptics (79.3%), the use of paper towels (38.9%), personal protective equipment such as face shields (46.9%), and safety containers for sharps and a separated space for the disposal of infectious waste (10.1%). Likewise, the following activities were found to be inadequately incorporated into the workflow of EMPs: education about infection control (77.5%), post-exposure management (35.9%), and the decontamination of items and spaces after use (88.4%). ICP were found to have a significant effect on the resources and activities of IPCPs (p<0.001). The resources and activities of IPCPs were found to be significantly different among the five cities (p<0.001). Conclusions: IPCPs for EMPs showed some limitations in their resources and activities. IPCPs should be actively supported, and specific IPCP activities for EMPs should be developed.